Characterization of Particulate Matter (PM2.5) in selected urban background and traffic sites in Metro Manila - BETITO, GRACE (Archīum Ateneo, 2018)
Short-term and long-term intensive particulate matter (PM) monitoring campaigns were undertaken at an urban background site (Manila Observatory, (MO UB)) and two roadside sites (Katipunan, Quezon City (KAT RS) and Taft Avenue, Manila City (TAFT RS)) in Metro Manila in 2015. Short-term measurement was conducted at the aforementioned sites during the Metro Manila Aerosol Characterization Experiment (MACE) from March to June, while the long-term monitoring was conducted only at MO UB from January to December. During the short-term field campaign, two samplers were deployed in parallel loaded with Teflon and quartz filters and operated for 24 hours; a total of 33 valid parallel samples were collected at the three sites. During the long-term measurement campaign, nuclepore filter samples were collected every Wednesday and Sunday using a Gent sampler. These filters were analyzed for mass concentration, elemental components, elemental and organic carbon, and major water-soluble ions. For the short-term chemical mass closure, eight aerosol types were considered. Results suggest that organic matter (OM) and elemental carbon (EC) were dominant in all sampling sites. High EC levels in roadside sites, especially in TAFT, suggest that a major fraction of the aerosols particle mass comes from traffic sources. The organic carbon to elemental carbon ratio (OC/EC) was lowest at the TAFT RS indicating a clear dominance of primary EC emissions resulting from incomplete combustion of fossil fuel. The higher OC/EC ratio in MO UB suggests the presence of secondary OC formation. The secondary inorganic aerosol (SIA) contribution to the total PM mass was comparable at the two roadside sites while higher contribution was measured for MO UB. Crustal matter contribution is comparable at the three sites. Sea salt and trace elements provide a rather small contribution to the PM mass. The chemical mass closure showed an excellent agreement between the gravimetric and the chemically-derived mass. Temporal variation (monthly, weekday/weekend) of PM2.5 for the yearlong dataset in MO UB were investigated. Using the species determined from the long-term measurement, PM sources and their contributions were identified using positive matrix factorization (PMF). Sources resolved by the model includes aged sea salt, ammonium sulfate, biomass burning, traffic, and brake wear. Using conditional probability function, likely direction of the PMF-resolved factors was influenced by prevailing monsoon and local sources.